Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13567-020-00751-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a new population of nasal surface macrophages and their susceptibility to PRRSV-1 subtype 1 (LV) and subtype 3 (Lena)

Abstract: Sialoadhesin (Sn) and CD163 have been recognized as two important mediators for porcine reproductive and respiratory syndrome virus (PRRSV) in host macrophages. Recently, it has been demonstrated that the highly virulent Lena strain has a wider macrophage tropism than the low virulent LV strain in the nasal mucosa. Not only CD163 + Sn + macrophages are infected by Lena but also CD163 + Sn − macrophages. This suggests that an alternative receptor exists for binding and internalization of PRRSV Lena in the CD163… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…However, the Schneiderian membrane has been shown to be osteogenic, since it harbors a niche of mesenchymal osteoprogenitor cells (Berbéri et al, 2017;Graziano et al, 2012;Gruber et al, 2004;Li et al, 2015). Furthermore, mucosal epithelia such as the Schneiderian membrane are known to contain high numbers of immune cells, including macrophages, because they form a primary defense against invading pathogens (Oh et al, 2020;Russell et al, 2015). In light of earlier results that have Interestingly, the mean area percentages of bone in available space for BCP N and ABG in the sheep study were comparable to the values obtained in the clinical study, while mean area percentages of residual graft material and combined bone and graft material were also similar for BCP N between the two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Schneiderian membrane has been shown to be osteogenic, since it harbors a niche of mesenchymal osteoprogenitor cells (Berbéri et al, 2017;Graziano et al, 2012;Gruber et al, 2004;Li et al, 2015). Furthermore, mucosal epithelia such as the Schneiderian membrane are known to contain high numbers of immune cells, including macrophages, because they form a primary defense against invading pathogens (Oh et al, 2020;Russell et al, 2015). In light of earlier results that have Interestingly, the mean area percentages of bone in available space for BCP N and ABG in the sheep study were comparable to the values obtained in the clinical study, while mean area percentages of residual graft material and combined bone and graft material were also similar for BCP N between the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Schneiderian membrane has been shown to be osteogenic, since it harbors a niche of mesenchymal osteoprogenitor cells (Berbéri et al, 2017; Graziano et al, 2012; Gruber et al, 2004; Li et al, 2015). Furthermore, mucosal epithelia such as the Schneiderian membrane are known to contain high numbers of immune cells, including macrophages, because they form a primary defense against invading pathogens (Oh et al, 2020; Russell et al, 2015). In light of earlier results that have suggested a role for macrophages in bone induction, it is possible that macrophages from the Schneiderian may have migrated to the nearby implanted bone grafts, and subsequently polarized to the pro‐regenerative M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, this isolate has been classified as an isolate of high virulence based on the severity of the clinical signs and lesions recorded in a study carried out in 3-week-old pigs in the respiratory model of the disease ( 44 ). Virulence might be a relevant characteristic because it has been demonstrated that PRRSV-1 isolates of higher virulence replicate more efficiently in the host ( 45 , 46 ) and in a wider range of cellular types ( 47 , 48 ), and it can be speculated that this better in vivo replication might help to overcome any previously existing immunity, either humoral or cellular.…”
Section: Discussionmentioning
confidence: 99%
“…Nauwynck’s group characterized macrophage populations in nasal mucosa, as this represents a primary entry site for many pathogens, including PRRSV [ 254 , 255 ]. These authors identified two major populations: CD163 + CD169 − cells, located in the upper lamina propria and within the epithelium, and CD163 + CD169 + cells, predominantly found in the deeper area of lamina propria , close to the cartilage.…”
Section: Origin and Plasticity Of Tissue-resident Macrophagesmentioning
confidence: 99%